from a handpicked tutor in LIVE 1-to-1 classes

# Find and correct the errors in the following mathematical statement. Substituting x = -3 in

(a) x^{2}+ 5x + 4 gives (-3)^{2} + 5(-3) + 4 = 9 + 2 + 4 = 15

(b) x^{2} - 5x + 4 gives (-3)^{2} - 5(-3) + 4 = 9 - 15 + 4 = -2

(c) x^{2} + 5x gives (-3)^{2} + 5(-3) = - 9 - 15 = -24

**Solution:**

An equation is a mathematical statement with an 'equal to' symbol between two algebraic expressions that have equal values.

a) x^{2}+ 5x + 4 gives (-3)^{2} + 5(-3) + 4 = 9 + 2 + 4 = 15

For x = -3

L.H .S = x^{2} + 5x + 4

= (-3)^{2} + 5(-3) + 4

= 9 -15 + 4

= 13 -15

= -2

But RHS is given as 15

Thus, L.H.S ≠ R.H.S

The correct statement is x^{2}+ 5x + 4 gives (-3)^{2} + 5(-3) + 4 = 9 -15 + 4 = -2

(b) x^{2} - 5x + 4 gives (-3)^{2} - 5(-3) + 4 = 9 - 15 + 4 = -2

For x = -3

x^{2} - 5x + 4

= (-3)^{2} - 5(-3) + 4

= 9 +15 + 4

= 28

But, RHS is given as -2

Thus, L.H.S ≠ R.H.S

The correct statement is x^{2} - 5x + 4 gives (-3)^{2} - 5(-3) + 4 = 9 + 15 + 4 = 28

(c) x^{2} + 5x gives (-3)^{2} + 5(-3) = - 9 - 15 = -24

For x = - 3

x^{2} + 5x

= (-3)^{2} + 5(-3)

= 9 -15

= - 6

But, RHS is given as -24

Thus, L.H.S ≠ R.H.S

The correct statement is x^{2} + 5x gives (-3)^{2} + 5(-3) = 9 - 15 = - 6

**☛ Check: **NCERT Solutions for Class 8 Maths Chapter 14

**Video Solution:**

## Find and correct the errors in the following mathematical statement. Substituting x = -3 in (a) x²+ 5x + 4 gives (-3)² + 5(-3) + 4 = 9 + 2 + 4 = 15 (b) x² - 5x + 4 gives (-3)² - 5(-3) + 4 = 9 - 15 + 4 = -2 (c) x²+ 5x gives (-3)² + 5(-3) = -9 - 15 = -24

Class 8 Maths NCERT Solutions Chapter 14 Exercise 14.4 Question 10

**Summary:**

The errors in the following mathematical statement are found by substituting x = -3 (a) x^{2}+ 5x + 4 gives (-3)^{2} + 5(-3) + 4 = 9 + 2 + 4 = 15 (b) x^{2} - 5x + 4 gives (-3)^{2} - 5(-3) + 4 = 9 - 15 + 4 = -2 (c) x^{2} + 5x gives (-3)^{2} + 5(-3) = -9 - 15 = -24. The corrected statements are (a) x^{2}+ 5x + 4 gives (-3)^{2} + 5(-3) + 4 = 9 -15 + 4 = -2 (b) x^{2} - 5x + 4 gives (-3)^{2} - 5(-3) + 4 = 9 + 15 + 4 = 28 (c) x^{2} + 5x gives (-3)^{2} + 5(-3) = 9 - 15 = - 6

**☛ Related Questions:**

visual curriculum